Pengaruh Pemanfaatan Teknologi dan Media Sosial sebagai Media Promosi Produk Terhadap Minat Generasi Z pada Bank Muamalat KCP Sumber - Aenutaqiah, Hilda; Djuwita, Diana; Rakim, Aditya Achmad (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2024)
This study aims to analyze the influence of the use of technology and social media on the interest of generation Z, as well as the influence of the use of technology and social media simultaneously or together on the interest of generation Z in Bank Muamalat KCP Sumber. This study uses a survey method with a quantitative approach. The data sources used include primary and secondary data. The population in this study is generation Z who are customers of Bank Muamalat KCP Sumber from 2017 to 2023 with a total of 7,500 customers. The number of samples taken was 100 respondents, which was determined using the Slovin formula, with purposive sampling techniques. Data were collected through observation, interviews, questionnaires, and documentation. This study used the Likert scale for measurement, and the data was analyzed using the IBM SPSS Statistic 29 application. The results show that the use of technology has a positive and significant influence on the interest of Generation Z in Bank Muamalat KCP Sumber, with a calculated t-value (3.624) greater than the t-table (1.66071) and a significance level of 0.001 which is smaller than 0.05. Social media also has a positive and significant influence on the interest of Generation Z in Bank Muamalat KCP Sumber, with a tcount value (6.746) greater than the t-table (1.66071) and a significance level of 0.001 which is smaller than 0.05. Together, the use of technology and social media has a significant effect on the interest of Generation Z with a contribution of 71.4%, while the remaining 28.6% is influenced by other variables.